Clinical decision rules: how to use them. Issue 3 (25th May 2010) - Phillips, B
Abstract : The first of this pair of papers outlined what a clinical decision rule is and how one should be created. This section examines how to use a rule, by checking that it is likely to work (examining how it has been validated), understanding what the various numbers that tell us about "accuracy" mean, and considers some practical aspects of how clinicians think and work in order to make that information usable on the front lines.